EFFECT OF SERVICE QUALITY AND PRICE ON BUYING DECISION ( Study of LBC Skin Care Bandung ) - Kurniawan, Ryan; Andrianto, Jairi; Nurhaiba, Nabila; Trirahayu, Nova; Ibrahim, Umar; Rizki, Kevin; Roespinoedji, Djoko (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this study was to analyze the effect of service quality and price on purchasing decision (case study at LBC Skin Care Clinic).The number of samples in this study were 96 respondents and using the method of non probability sampling. This research uses multiple linear regression test method. The results of this study indicate that there is simultaneous influence on service quality and price variables to purchase decision, seen from a significant value below 0.05 and Fcount > Ftable value. The result of this research also shows that the value of tcount in service quality variable and price is bigger than ttable, it can be stated that both variables have an influence on purchasing decision variable. In determination test there is influence of 39.1% from independent variable. Meanwhile, as much as 60.9% influenced by other variables.